Fundamentals of pesticides : - Ware, George W. (Thomson, 1986)
This chemical compositions and modes of action for pesticides are used in the agricultural and ornamental horticultural industry. The resource for studying for pesticide use licensing exams, with study questions embedded in the chapters.